Gut epithelial barrier dysfunction in lupus triggers a differential humoral response against gut commensals - Botía-Sánchez, María; Galicia, Georgina; Albaladejo-Marico, Lorena; Toro-Domínguez, Daniel; Morell, Maria; Marcos-Fernández, Raquel; Margolles, Abelardo; Alarcón-Riquelme, Marta E. (Frontiers in Immunology, 2023)
Systemic lupus erythematosus is an autoimmune disease with multisystemic involvement including intestinal inflammation. Lupus-associated intestinal inflammation may alter the mucosal barrier where millions of commensals have a dynamic and selective interaction with the host immune system. Here, we investigated the consequences of the intestinal inflammation in a TLR7-mediated lupus model. We found that lupus-associated intestinal inflammation modifies the IgA+ B cell response in the gut-associated lymphoid tissue in association with dysbiosis. Intestinal inflammation also alters the tight junction protein expression in the epithelial barrier, which correlates with increased paracellular permeability of the intestinal barrier. This permeability resulted in a differential systemic humoral response against intestinal commensals.